Endoscopic ultrasound-guided tissue sampling: How can we improve the results? - Alper, Emrah; Onur, İrem; Arabul, Mahmut; Ünsal, Belkıs (Turkish Journal of Gastroenterology, 2016)
Abstract Endoscopic ultrasound (EUS) enables a gastroenterologist to sample the masses of the middle and inferior mediastinum, which are adjacent to the esophagus; cystic or solid lesions of the pancreas, which are adjacent to the stomach and duodenum; and perirectal lesions. Needles used for EUS sampling include aspiration (19, 20, and 22 Gauge) or core biopsy needles (ProCore and Trucut) (19, 20, and 22 Gauge). The type and size of EUS needles do not alter the diagnostic results. Rapid on-site cytopathological evaluation will increase the diagnostic efficacy to 100% without prolonging the procedure time. Diagnostic efficacy of EUS-guided fine-needle aspiration or core biopsy depends on the experience of an endoscopist and a cytopathologist. In the presence of an experienced endoscopist and cytopathologist, the size of the needle does not have any significant impact on the diagnostic success.